PARMI (Production, Attention, Retention, Motivation, and Innovation): An alternative to improving scientific writing skills - Indrya Mulyaningsih; Sarwiji Suwandi; Budhi Setiawan; Mohammad Rohmadi (Lingua Cultura, 2018)
This research aimed to describe the development of scientific writing model based on PARMI. The stages included: creating prototypes; and developing models through four stages, focus group discussions, experts’ considerations, limited trials, and extensive trials. The research involved students and lecturers from STAIB (Islamic Bunga Bangsa Institute), STAIC (Islamic Institute of Cirebon), STAIMA (Islamic Institute of Ma’had Ali), and ISIF (Fahmina Institute of Islamic Studies) between July and December 2014. In these model included a philosophical foundation, either a concept or a principal; its application; and its effects. It finds that based on expert judgment, this model is feasible to be developed and piloted. The results of the limited trials provide some improvement, especially on the application of PARMI. Based on the results of extensive trials it can be concluded that PARMI can improve students’ ability in scientific writing.